An Enhanced Encryption System Based on the Unison of Lossless Compression and a Tri-Hashing Algorithm - Odim, Mba (My University, 2020)
In recent times, technological advancement in communications has made it essential to protect the ever-increasing amount of data and ensure the privacy of users. There is a lot of sensitive data present on the web, and it needs to be protected. Using conventional security methods like RSA, DES, AES algorithms, and others alone have become inadequate in protecting data from any kind of potential abuse. Complex algorithms are required to not only to encrypt the data but also to compress and distribute the data. This is due to the fact that some existing encryption techniques can be cracked given enough time and resources. This work attempts to resolve these flaws by combining a lossless compression technique with encryption in a single process or selective encryption of data. The proposed algorithm, tagged Enhanced Encryption System (EES), uses three different keys. One hashed from PBKDF2, the other from the PI sequence and finally DNA sequence, where each one is invariant of the user’s inputted key. Following this operation, there are infinite possible keys generated under every iteration. Lossless compression was applied to the test data based on the Lempel-Ziv-Welch (LZW) algorithm. Data encryption was implemented with the python programming language. The output produced different ciphertexts for the same plain text, thereby confusing any hacker that tries to brute-force the system. The experimental results showed that EES achieved better encryption and decryption run-time without losing data when compared to the AES, RSA and DES algorithms.
Keywords: Information Security; Ciphertext; Compression; Cryptography; Decryption; DNA; Encryption